(untitled) (Bangladesh Journal of Medical Education, 2023)
The study aimed to explore the level of stress of the primary-level health workers who are staying close-to-the community at Upazila-level in Bangladesh. This was a cross-sectional descriptive study with applications of both – qualitative and quantitative methods. Two upazilas were purposively selected and then stratified sampling technique was used to determine the sample size. A total of 172 health workers were selected covering a total of 11 occupational categories (doctors, nurses, midwives, pharmacists, medical assistants (SACMOs), medical technologists, health assistants, assistant health inspectors, family welfare assistants, family welfare visitor (FWV), and CHCPs. Regarding serving the COVID-19 probable cases, 57% said yes and regarding treatment to COVID-19 infected cases, 30% said yes. Regarding time spent on washing hand, about 52% said that they spent less than 30 seconds. During serving the patients, about 22% reported that they do not use PPE and 50% said that there is no arrangement of wearing PPE in their workplaces and 38% said that they do not follow standard procedures to wear. Regarding receiving COVID-19 related training, about 70% said ‘No’ and 73% said that they did not receive training on wearing PPE. Midwives and CHCPs were found to experience the highest level of stress at their workplaces. The most common stressors mentioned by the health workers were such as – dealing with difficult situation, sensitive to criticism, hunch for accuracy at work and inadequate resources. This study indicates that there is high prevalence (%) of stress among the primary level health workers in Bangladesh. Finally, the study recommends adopting an appropriate occupational stress management strategy at national level specific to the health workers working at the primary level as their nature of work is different to the secondary and tertiary level of care. Bangladesh Journal of Medical Education Vol.14(2) July 2023: 72-83